PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPENUMBER HEAD TOGETHER (NHT) DALAM MENINGKATKAN HASIL BELAJAR SISWAKELAS III-B PADA MATA PELAJARAN IPS DI SD NEGERI 064024 MEDAN SELAYANG TAHUN PEMBELAJARAN 2017/2018 - BARUS, KRISTINA SELLY BR (Unversitas Katolik Santo Thomas, 2018)
The problem in the research is the low learning result of Social Science (IPS) of natural and artificial environment in class III, one of the causal factor is the instructional model used by the teacher is less varied. The purpose of this study is to determine the implementation of learning and improvement of student learning outcomes by using cooperative learning model type Number Head Together (NHT). This research was conducted at State Elementary School 064024 Medan Selayang, with classroom action research. The subjects of the research are students of class III-B amounting to 25 students, while the object of research is to improve the learning result of Social Sciences (IPS) by using cooperative learning model type Head Head Together on Social Science subject. Data collection techniques used observations and tests. From the results of data analysis obtained the results of observation of the implementation of teacher activity learning in cycle I obtained the number of points 34 with a percentage of 68%. Observation of student activity cycle I obtained the number of points 26 with a percentage of 52%. The classical learning outcomes increased from 40.00% to 88.00% and the average value increased from 60.08 to 77.06. From the results of the study can be concluded the implementation of learning both categorized and student learningÂ outcomes increased after using cooperative learning model type Number HeadÂ together(NHT) on subjects Social Sciences material Natural and artificial environment in class III-B SD Negeri 064024 Medan Selayang.